Authentic assessment : a guide to implementation - Fischer, Cheryl Fulton; King, Rita M. (California : Corwin press, 1995)
This new book offers a clear, concise look at all key areas of authentic assessment and the strategies necessary for implementation. Fischer and King compare it to traditional testing and assessment and discuss how to develop and implement a program of your own. They show you how to establish goals, select the right activities, manage portfolio systems, and more. You will also learn ways to involve students, parents, and the community in the learning and assessment processes.
Includes bibliographical and references.
Keywords: Administrator Role. -- United States; Competence; Educational tests and measurements -- United States